Ramsey discounting of ecosystem services - Stefan Baumgärtner; Alexandra M. Klein; Denise Thiel; Klara Winkler (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
Most ecosystem services, which are essential for human well-being, are globally declining, while the production of consumption goods, measured by GDP, is still growing. To adequately account for this opposite development in public cost-benefit analyses, it has been proposed - based on a two-goods extension of the Ramsey growth model - to apply good-specific discount rates for manufactured consumption goods and for ecosystem services. Using empirical data for ten ecosystem services across five countries and the world at large, we estimated the difference between the discount rates for ecosystem services and for manufactured consumption goods. In a conservative estimate, we found that ecosystem services in all countries should be discounted at rates that are significantly lower than the ones for manufactured consumption goods. On global average, ecosystem services should be discounted at a rate that is 0.9-0.3 %-points lower than the one for manufactured consumption goods. The difference is larger in less developed countries and smaller in more developed countries. This result supports and substantiates the suggestion that public cost-benefit-analyses should use country-specific dual discount rates - one for manufactured consumption goods and one for ecosystem services.
Keywords: H43; Q28; Q51; Q57; 330; discounting; ecosystem services; (de)growth; heterogeneous consumption; Ramsey model; substitution